Legal Certainty in International Franchising: A Comparative Study between Indonesia and Singapore - Iman, Aini Nurul; Asiah, Nur; Lasabuda, Safa Nabila; Ramadhani, Sri Indah (SASI, 2025)
Introduction: The rapid expansion of international franchises into Indonesia creates complex legal dynamics, especially when foreign entities from developed countries such as Singapore face protectionist regulations in developing countries. One of the central issues that reflects this tension is the policy of limiting the number of foreign franchise outlets to a maximum of 250 outlets. These policies create ambiguity in legal norms, threaten legal certainty, and create potential conflicts between domestic market protections and international commitments within the global trade framework.Purposes of the Research: This study aims to examine and analyze legal certainty in cross-border franchise agreements, focusing on the comparison of the legal system between Indonesia and Singapore.Methods of the Research: Normative juridical approaches and comparative methods are used to explore differences in legal structures, the principle of freedom of contract, and the role of the state in regulating franchise schemes in both jurisdictions.Results of the Research: This study found that Singapore, with its minimalist common law approach, provides a high degree of contractual flexibility for business actors. On the contrary, the Indonesian legal system tends to be interventionist but does not fully guarantee legal certainty due to ambiguity of norms and overlapping regulations. Therefore, this study recommends the importance of harmonization of cross-border regulations in supporting the legal certainty of international franchise agreements.